2022
DOI: 10.1371/journal.pone.0267801
|View full text |Cite
|
Sign up to set email alerts
|

Spatial priorities for freshwater biodiversity conservation in light of catchment protection and connectivity in Europe

Abstract: Freshwater ecosystems host disproportionately high numbers of species relative to their surface area yet are poorly protected globally. We used data on the distribution of 1631 species of aquatic plant, mollusc, odonate and fish in 18,816 river and lake catchments in Europe to establish spatial conservation priorities based on the occurrence of threatened, range-restricted and endemic species using the Marxan systematic conservation planning tool. We found that priorities were highest for rivers and ancient la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Our results are reflective of wider pressures on freshwater catchments in south and east Europe, where conservation action is required due to growing threats from river regulation, dam construction, hydropower and climate change (Szabolcs et al, 2022). Steps to identify eel priority sites, improve connectivity to water supply dams where possible, and consider eel passability in the design for future dams during the construction phase could be of benefit here.…”
Section: Wider Implicationsmentioning
confidence: 78%
“…Our results are reflective of wider pressures on freshwater catchments in south and east Europe, where conservation action is required due to growing threats from river regulation, dam construction, hydropower and climate change (Szabolcs et al, 2022). Steps to identify eel priority sites, improve connectivity to water supply dams where possible, and consider eel passability in the design for future dams during the construction phase could be of benefit here.…”
Section: Wider Implicationsmentioning
confidence: 78%
“…Our results are reflective of wider pressures on freshwater catchments in south and east Europe, where conservation action is required due to growing threats from river regulation, dam construction, hydropower and climate change (Szabolcs et al, 2022).…”
Section: Wider Implicationsmentioning
confidence: 80%
“…The high infection prevalence and intensity of L3 and L4 gives evidence to the fact that A. crassus has adapted to Andalusian river and lagoon habitats, where there is abundance of intermediate and paratenic hosts, mainly copepods (Dangel et al, 2015), amphibians, small fish (Haenen & Van Banning, 1990), some of them harbouring acanthocephalans as internal parasites (Hohenadler et al, 2018; Weclawski et al, 2013), are an important part of the eel diet. This high biodiversity (Szabolcs et al, 2022), together with the fact that eels are predators of a wide variety of prey (Tesch, 2003), is the reason why A. crassus has been able to adapt to fluvial and lagoon ecosystems of Andalusia.…”
Section: Discussionmentioning
confidence: 99%
“…The high infection prevalence and intensity of L3 and L4 gives evidence to the fact that A. crassus has adapted to Andalusian river and lagoon habitats, where there is abundance of intermediate and paratenic hosts, mainly copepods (Dangel et al, 2015), amphibians, small fish (Haenen & Van Banning, 1990), some of them harbouring acanthocephalans as internal parasites (Hohenadler et al, 2018;Weclawski et al, 2013), are an important part of the eel diet. This high biodiversity (Szabolcs et al, 2022), together with the fact that eels are predators of a wide variety of prey (Tesch, 2003), is the rea- authors (Costa-Dias et al, 2010;Kirk et al, 2000;Nielsen, 1997), water salinity has not been found to be a determining factor for the prevalence and intensity of infection with A. crassus in the rivers analysed. A. crassus was more prevalent in eels captured in summer and autumn than in other months, which contrasts with many studies not registering any infection seasonality (Kennedy & Fitch, 1990;Möller et al, 1991;Molnár et al, 1994;Thomas & Ollevier, 1992;Würtz et al, 1998).…”
Section: Ta B L Ementioning
confidence: 99%